Growth and yield of sugarcane irrigated with brackish water and leaching fractions - Raquele M. de Lira; Ênio F. de F. e Silva; Djalma E. Simões Neto; José A. Santos Júnior; Breno L. de C. Lima; Jucicléia S. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective was to evaluate the growth and yield of sugarcane irrigated with brackish water and leaching fractions. A completely randomized experimental design was used, in a 5 x 2 factorial scheme, with four replicates. The treatments consisted of five irrigation water salinity levels (0.5, 2.0, 3.5, 5.0 and 6.5 dS m-1) and two leaching fractions (0 and 0.17), corresponding to 100 and 120% of the crop evapotranspiration. The irrigation management was performed daily. Irrigation water salinity levels were obtained by adding NaCl and CaCl2 to the public-supply water, in order to obtain a molar ratio between Na:Ca of 1:1. The following measurements were taken: height and stem diameter; number of tillers; number of leaves and leaf area with monthly frequency between 60 and 300 days after planting (DAP). It was concluded that irrigation water salinity negatively influenced the variables of growth and yield in the sugarcane, and the leaching fraction of 0.17 was capable of reducing the deleterious effects of the salts on the plants.